O antifeminismo: mapeamento dos discursos antagonistas do movimento feminista na internet - Zimberg, Gabriela (2018)
This research analyses how the antifeminist speeches have built their internet communication contracts. These speeches are mapped and submitted to the Discourse Analysis. Therefore, we present an antagonist panorama of feminism according to feminist scholars such as Judith Butler, Mary Hawkesworth, Clare Hemmings, Ronee Schreiber, Rita Terezinha Schmidt and Rachel Soihet. Hereinafter, we delimit a corpus search reflecting 19 posts of the social media Facebook, restricted to 2014-2017 timelag, whose intent is to display the antifeminist speech. We propose, based on these texts, a construction of a historical opposition between the feminist and antifeminist movements, guided by high-profile feminist events which have received extensive reaction on part of the antifeminists. At a third instant, we examine the antifeminist methods and their fiery precursors in the light of Ernesto Laclau´s discourse analysis, integrated with the theories of events and communication contracts by Aidar Prado and Algirdas Greimas, as well as Claude Zilberberg´s tensile semiotics. For the purpose of fulfilling the analysis, we introduced at the end an assay of poetry extremities grounded on Christine Mello´s theories, combined with additional observations from the cyberculture and social media studies accomplished by Adriana Amaral, Ivana Bentes, Raquel Recuero and Lucia Santaella